(untitled) - Newman, Barbara M.; Barbara M. Newman; Philip R. Newman (Australia,Belmont, CA, 2006)
This student resource includes a review of the chapter outline, a review of the learning objectives, a pre-test made up of multiple choice, matching, and short answer questions, a post-test, and "Suggestions for Further Observation and Study" which includes InfoTrac College Edition key words
Keywords: Developmental psychology